Establishment of Healthy Tolam Community (KOTOS): Community Empowerment Strategy in Improving Environmental Health Quality in Kuala Tolam Village - Kurniaman, Otang; Izzati, Salsabila; Ananda, Nur Huda; Ardiansyah, Isma; Afrilia, Bunga; Prayogo, Ego; Juliani, Juliani; Gunawan, Gunawan; Firmansyah, Ade Rizwan; Nelvani, Fina; Oktafira, Mimi; Kurnia, Indah; Andini, Jenita; Ningsih, Sri Wahyuni Karunia (CV. Rayyan Dwi Bharata, 2024)
The establishment of Komunitas Tolam Sehat (KOTOS) in Kuala Tolam Village is a community empowerment initiative that aims to improve health and environmental quality through a participatory approach. This article explores the process of community formation, the strategies used in community empowerment, as well as its impact on the health and environment of the village. Through a participatory approach, the community successfully engaged various elements of the community, including the village government, community leaders, and local residents, in designing and implementing health and environmental programs. The results show that this approach not only increases community awareness about the importance of health and environmental hygiene, but also strengthens social solidarity and community capacity to manage health issues independently and sustainably. This article highlights the importance of community empowerment in creating sustainable positive change at the local level.